Modelo de negocio para la creación de una empresa de monitoreo de contenedores de basura que contribuya a la adecuada gestión de la recolección de basura en la ciudad de Latacunga. - Panchi Guamangallo, Byron Paúl (2023)
The present development project arises from the need to know the filling levels of the garbage containers, due to the overflow and underutilization of these, for which it was proposed to develop a business model for the creation of a company monitoring of garbage containers through administrative strategies, which contributes to the proper management of garbage collection in the city of Latacunga. The research was carried out using a descriptive exploratory methodology, finding that for the creation of a technological company that starts with a new product, it is better adapted to the Lean Canvas model, since it focuses on the problem that the client has and the solution proposed in the project. Therefore, in order to know these aspects, an interview was carried out with the Latacunga Public Cleaning and Environmental Management Company - EPAGAL, where the minimum viable products and services were defined, such as: the creation of a mobile application and a web platform for the collection, storage and processing of information that will help the management of solid waste collection, providing information on the containers such as statistics on the percentage of garbage filling, emptying, washing, incidents, geographic location, among others. The components of the business model for the proposed company named FULL WASTE were developed, through the financial economic analysis an IRR of 29.85% and a NPV of USD 6430.4 were found, for which the proposal is considered feasible, and through the evaluation of the experts validated this development project.